STUDI PENERAPAN STANDAR KOMPETENSI LULUSAN DI SDN KALONGAN 01 UNGARAN TIMUR - Chory Praseptiana; Emmelia Maria Sulistyorini; Riska, Riska Bhinita Sari; Yustina Trihartatik; Sudjono, Sudjono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the application of graduate competency standards at SDN Kalongan 01 Ungaran Timur, based on (a) affective, (b) cognitive, (c) psychomotor aspects. The research subjects were school principals, teachers and staff employees. Seen at SDN Kalongan 01: (1) Students are not serious when praying (cognitive aspect) showing that students do not understand religious teachings, (2) Students are not yet responsible (affective aspect) seen when many students still break the rules, and (3) there are still many who cannot operate a computer (psychomotor aspect). After the research was carried out using observation, interviews and documentation. Then qualitative descriptive data analysis was carried out using the Miles and Huberman Interactive technique. The research results show that the implementation of graduate competency standards at SDN Kalongan 01 is good. It is proven in the education quality report that affective and cognitive competencies have been achieved well. However, the psychomotor aspect needs to be developed further.